2022
DOI: 10.7554/elife.70848
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming and redifferentiation of mucosal-associated invariant T cells reveal tumor inhibitory activity

Abstract: Mucosal-associated invariant T (MAIT) cells belong to a family of innate-like T cells that bridge innate and adaptive immunities. Although MAIT cells have been implicated in tumor immunity, it currently remains unclear whether they function as tumor-promoting or inhibitory cells. Therefore, we herein used induced pluripotent stem cell (iPSC) technology to investigate this issue. Murine MAIT cells were reprogrammed into iPSCs and redifferentiated towards MAIT-like cells (m-reMAIT cells). m-reMAIT cells were act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…MAIT cells are activated to produce cytokines such as IFN-γ and IL-17A in a TCR dependent and/or independent manner (Jesteadt et al, 2018, Leng et al, 2019, Rahimpour et al, 2015, Hinks and Zhang, 2020). Our recent study also found that redifferentiated MAIT cells from MAIT-iPSCs in vitro possessed similar properties (Sugimoto et al, 2022).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…MAIT cells are activated to produce cytokines such as IFN-γ and IL-17A in a TCR dependent and/or independent manner (Jesteadt et al, 2018, Leng et al, 2019, Rahimpour et al, 2015, Hinks and Zhang, 2020). Our recent study also found that redifferentiated MAIT cells from MAIT-iPSCs in vitro possessed similar properties (Sugimoto et al, 2022).…”
Section: Resultsmentioning
confidence: 79%
“…We previously established several iPSC clones derived from 5-OP-RU-loaded mouse MR1 tetramer (mMR1-tet) positive MAIT cells and confirmed that some clones possessed pluripotency through chimera formation (Sugimoto et al, 2022). Using the chimeric mice, we then attempted to generate novel C57BL/6 (B6) strains harboring rearranged TCR loci specific for MAIT cells.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…10,19 and demonstration of anti-tumor effects in various mouse models of MAIT immunotherapy. 20,21 In humans, there is an increase in frequency of circulating CD4+ MAIT cells and a subsequent decrease of CD8+ MAIT cells compared to healthy controls suggesting that CD8+ T cells are infiltrating tumor sites. 22 Our MAIT cell expansion protocol was able to mitigate the increase of frequency of CD4+ MAIT cells, thus possibly offering improved anti-tumor activity over previously-published protocols for MAIT expansion, which resulted in an increased frequency of CD4+ MAIT cells.…”
Section: Discussionmentioning
confidence: 99%